Beyond first-line therapy: efficacy and safety outcomes of continuing immunotherapy in extensive stage small cell lung cancer after PD-L1 inhibitor progression - Jianfeng Peng; Xueying Zhai; Xiaomei Liu; Zhaoqin Huang; Yimeng Wang; Peizhu Wu; Ran Gao; Xiangjiao Meng (Translational Oncology)
Objective: To evaluate the efficacy and safety of the continuing immunotherapy as subsequent therapy in extensive-stage small cell lung cancer (ES-SCLC) patients who have progressed after initial immunotherapy. Methods: A retrospective analysis was conducted on patients with ES-SCLC who experienced disease progression after receiving programmed cell death ligand 1 (PD-L1) inhibitors combined with standard chemotherapy as first-line treatment at three sites in China. Patients were divided into two groups according to whether to continue second-line immunotherapy. Results: In a cohort of 150 ES-SCLC patients evaluated post-progression following first-line PD-L1 inhibitors, second-line treatment regimens varied: 86 patients received immunotherapy beyond progression (IBP) and 64 did not proceed to second-line immunotherapy (non-IBP). IBP significantly increased both disease control rates (DCR, 68.6% vs. 32.8%, p<0.001) and overall response rate (ORR, 33.7% vs. 15.6%, p=0.012) and extended median progression-free survival (PFS, 4.1 vs. 2.4 months, HR=0.46, p<0.001) when compared with non-IBP group. The median overall survival (OS) in the IBP group was also longer than that in the non-IBP group (11.2 months vs. 9.0 months, HR=0.68, 95%CI 0.47-0.98, p=0.042). Subgroup analyses revealed a significant survival advantage with IBP treatment in patients presenting with baseline liver metastases, less than three metastatic organs, and those who were nonsmokers. Conclusions: In patients with ES-SCLC who received first-line PD-L1 inhibitors, continuing IBP extended second-line survival without increasing adverse events (AEs). A more pronounced OS benefit with IBP was noted within specific patient subgroups.